Strength exercise for football #3 – muscle development (definition, exercises, periodization) - Vuksanovikj, Vladimir; Aceski, Aleksandar; Tasevski Zikica; Spasovska, Katerina (Faculty of physical education sport and health, 2019)
The field of strength abilities, has different kinds of specialized trainings, that affect different subfields of the strength. The muscle building (hypertrophy) training is a part of subfield of strength, as well. This training for muscle development is important part of trainings for football game. The muscle building trainings in football, develop competitive players on the pitch. It is also important to develop other parts of strength abilities sub-fields. The muscle building training is most effective within young players after they will enter the maturity. Before the maturity, there will be almost no effects on muscle building body’s mechanisms. It is important to do at least 2 (not more than 3) trainings sessions, because this will be a supplement training in football. According our best practice, the period of competition is good period to implement muscle building training in football.
Вежби за силина во фудбалот #3 – развој на мускулна маса (дефиниција, вежби, периодизација)
Keywords: muscle mass; hypertrophy; training, soccer; periodization